Implementation of Flutter and Firebase in Developing a Mobile News Portal Application - Dio Azril Alfahri; Adi Widarma (Bigint Computing Journal, 2025)
The BPKAD PROVSU News Portal information system is a mobile application developed to facilitate the efficient dissemination of information and news to the public, as it can be accessed via smartphone anytime and anywhere. This application was designed using the Flutter framework and Firebase services, with system modeling based on the Unified Modeling Language (UML) and developed using the waterfall method. The research resulted in a functional application that enables fast and accurate information delivery. Testing using the black-box method confirmed that the system operates as expected. These findings indicate that the application can effectively improve public access to government-related news and information.